Measurement-and-analytical system for welding parameters and noise level during process of welded structures manufacture - Szubert, L.; Skoczewski, P.; Matusiak, J.; Wycislik, J. (Автоматическая сварка, 2016)
This paper presents the design, technical possibilities and intended use of the multi-station measurement-analytical system for assessing welding process parameters and noise levels. The system is an innovative solution as regards the measurement technique related to welding parameters and acoustic pressure in production floors. Once implemented industrially, the system enables the monitoring and recording of noise levels in individual work centres as well as the monitoring and recording of technological conditions accompanying welding of various structures and products.